Effects of Conceptual Titles on the Aesthetic Appreciation of Artistic Photographs - Duran Barraza, Gabriela (2022)
Conceptual information is central to the field of artistic photography. Nonetheless, there are very few studies on the matter. Therefore, we investigated whether artist’s conceptual titles affected viewers’ interest in artistic photographs. Experiment 1 showed that adding artist’s conceptual titles increased both the rated liking of and interest in the photographs, whereas adding a descriptive title had no effect. For Experiment 2 participants judged the pairing of photographs with artist-generated conceptual titles as more appropriate than plausible or random pairings, supporting the view that artist’s conceptual titles are an essential part of the artwork. In Experiment 3, interest was assessed by asking participants to place adjustable-size frames anywhere on the photographs. Participants selected more interest areas on photographs accompanied by conceptual titles than on those unaccompanied by titles. These findings support the hypothesis that conceptual information provided by the artist’s titles increases interest and liking in photographs.